Qualitative comparison of decalcifiers for mouse bone cryosections for subsequent biophotonic analysis - Shibarjun Mandal; Ramya Motganhalli Ravikumar; Astrid Tannert; Annett Urbanek; Rustam R. Guliev; Max Naumann; Sina M. Coldewey; Uta Dahmen; Lina Carvalho; Luís Bastião Silva; Ute Neugebauer (Scientific Reports)
Abstract Bone tissue, with its complex structure, often necessitates decalcification of the hard tissue for ex vivo morphological studies. The choice of a suitable decalcification method plays a crucial role in preserving desired features and ensuring compatibility with diverse imaging techniques. The search for a universal decalcification method that is suitable for a range of biophotonic analyses remains an ongoing challenge. In this study, we systematically assessed five standard bone decalcification protocols, encompassing strong mineralic acids (3% and 5% nitric acid), a commercially available formulation of hydrochloric and formic acid), as well as weak organic acids (5% trichloroacetic acid and 8% formic acid), and a chelating agent (25% ethylenediamine-tetraacetic acid) with varying decalcification durations, using mouse long bones as our experimental model. Our imaging analysis panel included classical histological staining (Hematoxylin and Eosin, H&E), immunofluorescence staining, and label-free Raman microspectroscopic imaging. We used cryosections instead of paraffin sections since paraffin interferes with tissue Raman signals. This approach is not as commonly used as it is more prone to handling artifacts, but is the preferred method for subsequent Raman analysis. Decalcification efficacy was evaluated based on various qualitative and some quantitative imaging parameters by 2–3 independent observers. Our systematic approach revealed that the chelating agent, when used for 24 h, optimally preserved bone features and, thus, would be the ideal decalcifying agent for comprehensive subsequent analysis. However, the choice of decalcifier and the ideal decalcification duration may vary depending on the type and thickness of bone, necessitating tailored adjustments to meet specific experimental requirements.